Integration of CNTs in 3D-IC interconnects: a non-destructive approach for the precise characterization and elucidation of interfacial properties - Ghosh, K. (2016)
Having an array of novel functionalities and performance advantages, Multi-Walled Carbon Nanotubes (MWCNT) are one of the most promising nanomaterials to replace metals like copper and aluminum in the low-dimensional interconnects in three-dimensional (3D) integrated circuits (3D-IC) and sensors. Low resistivity, large current density, high thermal conductivity (10 times that of copper), and a low coefficient of thermal expansion (CTE) make MWCNTs a prime choice for integration in next-generation 3D-chip stacks. However, the growth of carbonaceous nanomaterials on top of metals gives rise to issues of high interfacial resistance at the metal/MWCNT interfaces due to large differences in their potential work functions. Although it has become feasible to grow vertically aligned MWCNTs on metal lines, it has not been possible to systematically and precisely determine the interfacial contact resistance values between the as-grown single-, or bundle-MWCNTs and the base metal-lines. Here, we report a novel experimental method for the measurement of metal/carbon interface contact resistance with the aid of nanoprobing setup, thereby eliminating undesirable metal-pad deposition step required in conventional techniques. In the present approach, nanoprobes are placed in contact with individual CNT-bundles making direct electrical contacts. Two-point-probe (2PP) and four-point-probe (4PP) measurements are systematically performed to accurately estimate values of the contact resistance at the metal/CNT interface. The as-measured interfacial contact resistance for a bundle in 2–5 μm diameter oxide-via is found to be ∼730 Ω, while on a per-CNT basis the metal/MWCNT contact resistance is ∼35 kΩ. The reported values of interfacial contact resistance are quite lower than those reported elsewhere in the literature. The characteristic novelty of current experimental approach lies in the total elimination of any steps, involving further chemical, mechanical or physical processing, which cause deformation and/or damage to the intrinsic properties and morphology of as-grown CNT-bundles. Uniquely, no alteration needs to be made to properties or environment of as-grown MWCNTs. The advantages of this approach results in relatively more accurate and error-free determination of the metal/CNT interfacial resistance values than any of earlier techniques.